Formulation and In Vitro Evaluation of the Anticholesterol Activity of Effervescent Granules Containing Ethanolic Extract of Lempipi Leaves (Gymnema inodorum (Lour.) Decne) - Nurwani Purnama Aji; Tri Yanuarto; Zahra Salsabilla; Putri Dewi Sartika (Gayaku Publisher, 2026)
Background: Hypercholesterolemia is one of the major risk factors for cardiovascular disease, with an increasing prevalence in Indonesia. The use of natural products as alternative therapies represents a promising approach. Lempipi leaves (Gymnema inodorum (Lour.) Decne) contain bioactive compounds, including flavonoids, saponins, tannins, and alkaloids, which may exhibit anticholesterol activity. Objective: This study aimed to formulate effervescent granules containing ethanolic extract of lempipi leaves and evaluate their physical quality and in vitro anticholesterol activity.Methods: Lempipi leaves were collected, processed into dried simplicia, and extracted by maceration using 96% ethanol. The resulting extract was formulated into effervescent granules. Physical quality evaluations included organoleptic properties, flow time, angle of repose, particle size distribution, degree of fineness, foam height, pH, and solubility. In vitro anticholesterol activity was assessed using a UV–Visible spectrophotometer at a wavelength of 627 nm. The activity was determined based on the percentage of inhibition and the half-maximal effective concentration (EC₅₀). Results: All effervescent granule formulations met the required physical quality standards. Formula 1 showed an EC₅₀ value of 125.587 ppm, indicating weak anticholesterol activity, whereas Formula 2 showed an EC₅₀ value of 76.99 ppm, indicating moderate anticholesterol activity. Formula 2 demonstrated stronger anticholesterol activity than Formula 1. Conclusion: Effervescent granules containing ethanolic extract of lempipi leaves exhibited in vitro anticholesterol activity and met the physical quality requirements. Formula 2 showed the highest activity and has the potential to be further developed as a herbal preparation to help reduce cholesterol levels. Suggestion: Further studies are recommended to optimize the formulation, determine the active compounds responsible for the anticholesterol effect, evaluate product stability, and conduct in vivo and clinical studies to confirm its efficacy and safety.